2010
DOI: 10.1016/j.neuroimage.2010.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Discovering genetic associations with high-dimensional neuroimaging phenotypes: A sparse reduced-rank regression approach

Abstract: There is growing interest in performing genome-wide searches for associations between genetic variants and brain imaging phenotypes. While much work has focused on single scalar valued summaries of brain phenotype, accounting for the richness of imaging data requires a brain-wide, genome-wide search. In particular, the standard approach based on mass-univariate linear modelling (MULM) does not account for the structured patterns of correlations present in each domain. In this work, we propose sparse Reduced Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
240
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(242 citation statements)
references
References 40 publications
1
240
0
1
Order By: Relevance
“…Reduced rank regression 120 (Vounou et al, 2010;Izenman, 1975) is a related multi-output linear-regression. Unlike CCA, it does not discard explained variance during model fitting.…”
Section: Related Workmentioning
confidence: 99%
“…Reduced rank regression 120 (Vounou et al, 2010;Izenman, 1975) is a related multi-output linear-regression. Unlike CCA, it does not discard explained variance during model fitting.…”
Section: Related Workmentioning
confidence: 99%
“…In addition to voxelwise maps of FA, tract-and fiber-based measures from diffusion imaging may also be considered as predictive outputs. Such measures, along with multivariate methods that simultaneously consider not only multiple genes, but also multiple voxels (Vounou et al, 2010;Hibar et al, 2011b;Wan et al, 2011) may help provide more statistical power. For instance, our voxelwise, multilocus model improved only slightly beyond the 2-SNP model with polymorphisms in NTRK1 and CLU.…”
Section: Discussionmentioning
confidence: 99%
“…To address this problem, penalized CCA and related methods were introduced by employing sparse penalties to select a small number of features. Examples include sparse CCA (Parkhomenko et al, 2009;Witten and Tibshirani, 2009), sparse PLS (Chun and Keles¸, 2010) and sparse reduced rank regression (Vounou et al, 2010), which have been demonstrated to be effective in detecting multivariate genomic and brain imaging associations (Grellmann et al, 2015;Liu and Calhoun, 2014). To incorporate biological prior knowledge and data structures to guide the search of associations, group SCCA (Lin et al, 2014) and network-guided sparse reduced rank regression (Wang et al, 2014) were proposed, which can further improve variable selection.…”
Section: Introductionmentioning
confidence: 99%